Assessment of the preparedness and acceptability for distance learning: A guide for an efficient distance learning - Argarin, Jesus; Argarin, Jessica Arah (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
A shift in the mode of learning has shifted from face-to-face to online and modular learning, wherein the former has been utilized more. The fundamental goal of the research is to explore the experiences of students along with their recommendations to further improve the delivery of physical education online class using what gadget is the best and much more efficient base on their experienced. This study assessed the preparedness and acceptability of University of Makati (UMak) students with a bachelor’s degrees in physical wellness on distance learning. The study employed the quantitative method of research wherein the researcher used related research questions. The data were through the questionnaires. It served as a survey tool to draw facts about the preparedness and acceptability of University of Makati students with a bachelor’s degrees in physical wellness on distance learning. The respondents of the study bachelor’s degree in physical wellness students at the University of Makati. The researchers used the student’s evaluation as an instrument to complement the research questions in assessing the competency of gadgets used. Based on the results of the study, majority of the respondents are prepared for any distance learning, however, the reliability of the gadget and availability of connectivity at home are issues that need solution. Majority of the students with a percentage rating ranging from 88% to 95% accept the possibility of having distance learning as the method to be used by UMak-CHK department on the 2nd semester of 2021-2022. The result of the assessment of the readiness and competency of faculty in the delivery of distance learning will be used as a tool in the implementation of courses of action in preparation for the coming semester of AY 2021-2022.